Ретроспективная оценка состояния периодонта опорных зубов под несъемными протезами (Эндодонтия Today)
There were studied follow-up results of orthopedic treatment of 150 patients with traditional and modern constructions of dental prosthesis. There were discovered dynamics of changes in periodontal status of abutment teeth in various conditions after finishing of prosthetics, including dependence on obturation character of tooth root canal and method of prosthetics.